Impact of an antimicrobial stewardship programme on reducing broad-spectrum antibiotic use and its effect on carbapenem-resistant Acinetobacter baumannii (CRAb) in hospitals in Jordan. (21st November 2020) - Yusef, Dawood; Hayajneh, Wail A; Bani Issa, Ali; Haddad, Rami; Al-Azzam, Sayer; Lattyak, Elizabeth A; Lattyak, William J; Gould, Ian; Conway, Barbara R; Bond, Stuart; Conlon-Bingham, Geraldine; Aldeyab, Mamoon A
Abstract: Objectives: To evaluate the impact of an antimicrobial stewardship programme (ASP) on reducing broad-spectrum antibiotic use and its effect on carbapenem-resistant Acinetobacter baumannii (CRAb) in hospitalized patients. Methods: The study was a retrospective, ecological assessment in a tertiary teaching hospital over 6 years (January 2014 to December 2019). The intervention involved the implementation of an ASP in February 2018, which remains in effect today. This ASP consists of several components, including education, antibiotic guidelines, antibiotic restriction policy with prior approval, audit of compliance to the restriction policy and feedback. Restricted antibiotics were imipenem/cilastatin, ertapenem, meropenem, vancomycin, teicoplanin, tigecycline, colistin, amikacin, piperacillin/tazobactam, levofloxacin and ciprofloxacin. The intervention was evaluated by time-series methods. Results: Statistically significant decreases in the level of antibiotic use, after the introduction of the ASP, were observed for the following antibiotics: imipenem/cilastatin ( P  = 0.0008), all carbapenems ( P  = 0.0001), vancomycin ( P  = 0.0006), colistin ( P  = 0.0016) and third-generation cephalosporins ( P  = 0.0004). A statistically significant decrease in the slope, after the introduction of the ASP, for ertapenem ( P  = 0.0044) and ciprofloxacin ( P  = 0.0117) was observed. For piperacillin/tazobactam, there was a significant increasing trend ( P  = 0.0208) before the introduction of the ASP. However, this increased trend was halted post-introduction of the ASP ( P  = 0.4574). The introduction of the ASP was associated with a significant impact on reducing the levels of CRAb ( P  = 0.0237). Conclusions: The introduced antimicrobial stewardship interventions contributed to a reduction in the use of several broad-spectrum antibiotics, reversed the trends of increasing use of other antibiotics and were associated with a significant reduction in CRAb.